Factors associated with emergency department length of stay of internal medicine patients - Sanne Vonk (Emergency Care Journal, 2021)
Emergency Department (ED) Length Of Stay (ED-LOS) is associated with quality of care, patient safety and treatment outcome. The aim of this study is to identify factors associated with ED-LOS of internal medicine patients and provide recommendations to shorten ED-LOS. A retrospective cohort study was conducted in a single center in the Netherlands. Anonymised data of 7,380 ED attendances from January 2016 to January 2018 were analyzed. Data included time of ED arrival and departure, sex, age, source of referral, triage category, first or consecutive visit and number of radiological examinations. Univariate analyses were used. Mean ED-LOS was 220 minutes. Factors which significantly prolonged ED-LOS were older age, source of referral, triage category, need for admission, first visit, number of radiological examinations, presentation in winter or spring and time of arrival (day and evening). Several patient and circumstantial factors are associated with ED-LOS. To shorten ED-LOS, we recommend to anticipate need for admission for older patients who arrive by ambulance and to create time slots in the radiology program and to restructure the morning report.